2013
DOI: 10.1159/000368838
|View full text |Cite
|
Sign up to set email alerts
|

Peroneal and Tibial Intraneural Ganglion Cysts in Children

Abstract: Background/Aims: Intraneural ganglion cyst is a rare and underrecognized clinical entity in the pediatric population, which may cause pain as well as motor and sensory neurological deficits. This study presents 4 pediatric patients harboring ganglion cysts involving the peroneal and tibial nerves. Methods: Data encompassing pre- and postoperative analyses of 4 pediatric patients with intraneural ganglion cyst was evaluated. Results: Out of these 4 patients, 3 had an intraneural ganglion cyst involving the pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Intraneural ganglion cysts usually occur in adults [2]. However, one of our cases showed that the disease can also occur in children and adolescents as also described in other cases [16,17].…”
Section: Discussionsupporting
confidence: 77%
“…Intraneural ganglion cysts usually occur in adults [2]. However, one of our cases showed that the disease can also occur in children and adolescents as also described in other cases [16,17].…”
Section: Discussionsupporting
confidence: 77%
“…Although our patient appeared to have an important functional deficit with an almost complete paralysis, an important motor recovery was observed at the 2-month post-operative follow-up, despite the consistent volume of the cyst and the acute appearance of drop foot. Other authors report partial recoveries after 3 months [13,21], while others report the persistence of slight motor deficits several months after surgery [21,27]. However, there appear to be motor recoveries even seventeen months after surgery [28].…”
Section: Discussionmentioning
confidence: 97%
“…Similar to the cases reported by Williams [14] and Stamiris [10], rehabilitative treatment seems to improve the clinical outcomes and, in our case, prompt surgical treatment may have further affected the complete motor recovery. However, even in cases where the symptoms last for months, it may be useful to refer for surgery [21]. A palpable mass lateral to the fibula head may be present [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, two out of three patients with affection of the peroneal nerve had a preserved motor function preoperative which improved during the follow-up. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Most commonly patients present with a foot drop with subsequent high stepping gait and associated sensory deficits. 5 6 …”
Section: Introductionmentioning
confidence: 99%